Adult Periodic Alternating Nystagmus Masked by Involuntary Head Movements - Kaski, Diego; Haider, Salman; Male, Amanda; Radunovich, Alex; Liu, Fan; Cordivari, Carla; Bhatia, Kailash P.; Bronstein, Adolfo M. (Frontiers in Neurology, 2018)
N/A